Distinctive behaviour of live biopsy-derived carcinoma cells unveiled using coherence-controlled holographic microscopy - Gál, Břetislav; Veselý, Miroslav; Čolláková, Jana; Nekulová, Marta; Jůzová, Veronika; Chmelík, Radim; Veselý, Pavel (PloS one, 2017)
Head and neck squamous cell carcinoma is one of the most aggressive tumours and is typically diagnosed too late. Late diagnosis requires an urgent decision on an effective therapy. An individualized test of chemosensitivity should quickly indicate the suitability of chemotherapy and radiotherapy. No ex vivo chemosensitivity assessment developed thus far has become a part of general clinical practice. Therefore, we attempted to explore the new technique of coherence-controlled holographic microscopy to investigate the motility and growth of live cells from a head and neck squamous cell carcinoma biopsy. We expected to reveal behavioural patterns characteristic for malignant cells that can be used to imrove future predictive evaluation of chemotherapy. We managed to cultivate primary SACR2 carcinoma cells from head and neck squamous cell carcinoma biopsy verified through histopathology. The cells grew as a cohesive sheet of suspected carcinoma origin, and western blots showed positivity for the tumour marker p63 confirming cancerous origin. Unlike the roundish colonies of the established FaDu carcinoma cell line, the SACR2 cells formed irregularly shaped colonies, eliciting the impression of the collective invasion of carcinoma cells. Time-lapse recordings of the cohesive sheet activity revealed the rapid migration and high plasticity of these epithelial-like cells. Individual cells frequently abandoned the swiftly migrating crowd by moving aside and crawling faster. The increasing mass of fast migrating epithelial-like cells before and after mitosis confirmed the continuation of the cell cycle. In immunofluorescence, analogously shaped cells expressed the p63 tumour marker, considered proof of their origin from a carcinoma. These behavioural traits indicate the feasible identification of carcinoma cells in culture according to the proposed concept of the carcinoma cell dynamic phenotype. If further developed, this approach could later serve in a new functional online analysis of reactions of carcinoma cells to therapy. Such efforts conform to current trends in precision medicine.
Keywords: Male; Microscopy; lidé středního věku; Tumor Cells, Cultured; mikroskopie; Tumor Suppressor Proteins; holografie; nádorové biomarkery; Cell Movement; Head and Neck Neoplasms; Humans; Immunohistochemistry; Middle Aged; nádorové supresorové proteiny; senioři; Biomarkers, Tumor; Carcinoma, Squamous Cell; Transcription Factors; mužské pohlaví; buněčný cyklus; Aged; Cell Cycle; spinocelulární karcinom; nádorové buňky kultivované; transkripční faktory; Biopsy; imunohistochemie; Holography; pohyb buněk; nádory hlavy a krku; lidé; biopsie